2020
DOI: 10.1016/j.wdp.2020.100242
|View full text |Cite
|
Sign up to set email alerts
|

Citizen participation dilemmas in water governance: An empirical case of Kumasi, Ghana

Abstract: Highlights Citizen participation offers a valuable pathway for equitable and sustainable water delivery. There is an increase in institutional search for ideal approaches to enhance local inputs in water decisions. Findings from the study show that citizens are willing to participate in decision-making on water-related process. Ghana Water Company Limited (GWCL) focuses more on the technical aspect of water delivery than the social aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Also, NWP specifies the approaches in which organisations and local government can share the responsibilities in the planning, design, and management of water resources with local communities. The recognition of local-level participation is anchored by the principle of subsidiarity which encourages the lowest appropriate level in society to participate in decisions that affect them actively (Okyere et al, 2019;Erdiaw-Kwasie et al, 2020). However, this study found that the translation of the NWP's policy goals on local resident participation in water governance programs remains a major challenge.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Also, NWP specifies the approaches in which organisations and local government can share the responsibilities in the planning, design, and management of water resources with local communities. The recognition of local-level participation is anchored by the principle of subsidiarity which encourages the lowest appropriate level in society to participate in decisions that affect them actively (Okyere et al, 2019;Erdiaw-Kwasie et al, 2020). However, this study found that the translation of the NWP's policy goals on local resident participation in water governance programs remains a major challenge.…”
Section: Discussionmentioning
confidence: 82%
“…Here, as in studies elsewhere, the medium of engagement (e.g. community meetings) matters when active and full participation of beneficiaries in community-based water projects is envisaged (Adams & Zulu, 2015;Finewood, 2016, Erdiaw-Kwasie et al, 2020. Also, residents of Piase indicated that they were actively engaged during project evaluation because it was a major condition for additional funding by partners.…”
Section: Discussionmentioning
confidence: 85%
“…Isto sugere uma atenção multinível da condição que os sistemas terão de responder aos cenários de mudanças e a forma que as decisões serão tomadas e implementadas. A presença dessas características associadas à governança das águas sugere uma maior habilidade dos sistemas conseguirem responder às transições no âmbito ecológico (Gunderson, 2000), fortalecer a tomada de decisão com o conhecimento e aceitação dos atores pertencentes ao sistema (Porras et al, 2019;Erdiaw-Kwasie et al, 2020), além de equidade e justiça nas ações acordadas.…”
Section: Resultados E Discussõesunclassified
“…Complicating matters further, cities in Sub‐Saharan Africa are considered to be among the most vulnerable to health disasters owing to the old but persistent structural ills of ‘urbanisation without development’ (Boadi et al, 2005, p. 465), inadequate planning for health disasters (Cobbinah, Erdiaw‐Kwasie, and Adams, 2021), a lack of integration of urban planning and public health interventions (Anaafo, Owusu‐Addo, and Takyi, 2021), and deficits in basic infrastructure, such as the water supply and sanitation (Satterthwaite, Sverdlik, and Brown, 2019; UN‐Habitat, 2020). These persist amidst weak governance systems—characterised by ineffective planning and coordination with sector agencies—and inadequate resources to confront proactively the structural challenges that expose residents to health disasters (Dodman et al, 2017; Erdiaw‐Kwasie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%